P08.26 The impact of education on australian practice nurses' knowledge and attitudes in relation to chlamydia testing: findings from the australian chlamydia control effectiveness pilot (accept). (13th September 2015) - Lorch, R; Guy, R; Temple-Smith, M; Vaisey, A; Wood, A; Ford, B; Murray, C; Bourne, C; Hall, M; Hocking, J
Abstract : Introduction: ACCEPt is a randomised controlled trial of annual chlamydia testing for 16–29 year olds in general practice. Part of the trial examines whether practice nurses (PNs) can play a role in chlamydia testing. PNs previously identified education as an important facilitator to their involvement in testing. We evaluated the impact of education on PNs' knowledge and attitudes in relation to chlamydia testing. Methods: The 2-hour education program was delivered at clinics to PNs by ACCEPt staff. A survey was conducted at baseline and repeated 6–12 months post education; analysis focused on PNs who completed both surveys. The survey used Likert scales, which were analysed as continuous variables (scores). We used t-tests to assess if changes in mean scores between survey rounds were greater in the education group. Results: In total 72 PNs completed both surveys (42 of which received education). Changes in mean scores between survey rounds in the education group were significantly different to the non-education group for the statements: most chlamydia infections in men are asymptomatic (p = 0.01); I would offer a chlamydia test to a 23-year old married female having a pap test (p = 0.04); I would like to be more involved in testing (p = 0.04); I would like to be more involved with managing a recall/reminder system (p = 0.05); and time/workload constraints are barriers to testing (p = 0.001). The increases in mean knowledge score (p < 0.01) and mean barrier score (p = 0.03) were greater in education group. Conclusion: Our evaluation suggests PN participation in the ACCEPt education program improved chlamydia testing knowledge and attitudes among PNs and could be utilised more widely across primary care. The findings also suggest time/workload constraints became a stronger barrier after education, presumably due to greater involvement in testing. Future analyses will determine if the education program combined with other initiatives have increased testing rates. Disclosure of interest statement: ACCEPt was commissioned and funded by the Australian Government Department of Health and Ageing. Additional funding has been received from the National Health and Medical Research Council, the Victorian Department of Health and NSW Health.